2016
DOI: 10.1245/s10434-016-5595-3
|View full text |Cite
|
Sign up to set email alerts
|

Women with Low-Risk DCIS Eligible for the LORIS Trial After Complete Surgical Excision: How Low Is Their Risk After Standard Therapy?

Abstract: Background Identifying DCIS patients at low risk for disease progression could obviate need for standard therapy. The LORIS (surgery versus active monitoring for low-risk DCIS) trial is studying the safety of monitoring low-risk DCIS, although ipsilateral breast tumor recurrence (IBTR) rates in patients meeting enrollment criteria after complete surgical excision are unknown. Methods Women with pure DCIS treated with breast-conserving surgery (BCS) with/without radiation therapy (RT) from 1/1996–1/2011 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…22 Further, among women with DCIS who continued to meet LORIS criteria even after examination of the complete surgical excision specimen, the 10-year IBE rate was a substantial 12.1%. 23 Our current data show that in our entire population of women with very low-volume DCIS, and in the subsets of those age ≥50 years and those with low-grade DCIS, risk of IBE was clinically significant at 10-years: 12.3% (entire population), 12.6% (age ≥50 years), and 14.6% (low grade, including cases borderline between ADH and DCIS), respectively. In our 207 mDCIS patients not receiving radiation, all of whom underwent surgical excision demonstrating complete DCIS removal by the core biopsy, the 10-year IBE rate was 14.7%, and in the subset with low-grade DCIS, 13.9%.…”
Section: Discussionmentioning
confidence: 52%
“…22 Further, among women with DCIS who continued to meet LORIS criteria even after examination of the complete surgical excision specimen, the 10-year IBE rate was a substantial 12.1%. 23 Our current data show that in our entire population of women with very low-volume DCIS, and in the subsets of those age ≥50 years and those with low-grade DCIS, risk of IBE was clinically significant at 10-years: 12.3% (entire population), 12.6% (age ≥50 years), and 14.6% (low grade, including cases borderline between ADH and DCIS), respectively. In our 207 mDCIS patients not receiving radiation, all of whom underwent surgical excision demonstrating complete DCIS removal by the core biopsy, the 10-year IBE rate was 14.7%, and in the subset with low-grade DCIS, 13.9%.…”
Section: Discussionmentioning
confidence: 52%
“…A retrospective study by Pilewskie et al . evaluated the risk of ipsilateral tumour recurrence after BCS with or without radiotherapy for women who met the inclusion criteria for the LORIS trial and found that 24 of 401 (6.0%) patients experienced an ipsilateral recurrence.…”
Section: Current Trials Of Low‐risk Dcismentioning
confidence: 99%
“…Most articles accurately stated that the mortality rate from dcis is low (3%) and that mortality was equivalent regardless of treatment type. Nevertheless, many commentators misinterpreted the finding of low mortality to infer either that dcis is a precursor, and not a cancer [15][16][17][18] ; that dcis is overdiagnosed and does not need to be treated (that is, "watch and wait") [19][20][21][22][23][24][25][26][27][28][29] ; or that dcis is overtreated (that is, omit radiotherapy) [30][31][32][33][34] . Most troubling from our point of view was that several commentators interpreted the finding that the increased risk of death from breast cancer in dcis patients who developed an ipsilateral invasive recurrence justified efforts to prevent the invasive ipsilateral recurrence as a life-saving measure [35][36][37][38][39][40][41][42][43] .…”
Section: Citations In the Medical Literaturementioning
confidence: 99%
“…For example, Pilewskie et al 15 cite our paper in support of the statement that "ductal carcinoma in situ (dcis) is a noninvasive breast lesion with no theoretic metastatic potential and excellent survival"; Shieh et al 16 deem dcis "likely to be a true precursor lesion" rather than a cancer; Ganz et al 17 note that treatment for dcis is "thought of as breast cancer prevention, because ductal carcinoma in situ is rarely lethal"; and Masood et al 18 suggest that our paper "raises the question of why we are calling an entity 'cancer' when it does not act like a malignant lesion," which is "sufficient evidence to consider a definitive change in the use of the term 'carcinoma in situ' and replace it with a less threatening terminology." It is interesting to note that in regard to that issue (and the three other issues discussed in the subsections that follow), none of the commentators actually said that we were wrong-that is, that dcis is not a fully-fledged cancer.…”
Section: Dcis Is a Precursor Not Cancermentioning
confidence: 99%